A Multidimensional Diversity‐Oriented Synthesis Strategy for Structurally Diverse and Complex Macrocycles. Issue 37 (3rd August 2016) - Nie, Feilin; Kunciw, Dominique L.; Wilcke, David; Stokes, Jamie E.; Galloway, Warren R. J. D.; Bartlett, Sean; Sore, Hannah F.; Spring, David R.
Abstract: Synthetic macrocycles are an attractive area in drug discovery. However, their use has been hindered by a lack of versatile platforms for the generation of structurally (and thus shape) diverse macrocycle libraries. Herein, we describe a new concept in library synthesis, termed multidimensional diversity‐oriented synthesis, and its application towards macrocycles. This enabled the step‐efficient generation of a library of 45 novel, structurally diverse, and highly‐functionalized macrocycles based around a broad range of scaffolds and incorporating a wide variety of biologically relevant structural motifs. The synthesis strategy exploited the diverse reactivity of aza‐ylides and imines, and featured eight different macrocyclization methods, two of which were novel. Computational analyses reveal a broad coverage of molecular shape space by the library and provides insight into how the various diversity‐generating steps of the synthesis strategy impact on molecular shape. Abstract : A diversity‐oriented synthesis : A four‐stage multidimensional strategy for the synthesis of complex, highly functionalized and structurally diverse macrocycles is reported (see picture). The synthesis exploits the diverse reactivity of aza‐ylides and imines and features eight different macrocyclization methods, two of which are novel.